2004
DOI: 10.1590/s0100-879x2004001000007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bullfrog (Rana catesbeiana) oil administered by gavage on the fatty acid composition and oxidative stress of mouse liver

Abstract: The aim of the present study was to investigate the effects of daily intragastric administration of bullfrog oil (oleic, linoleic and palmitoleic acid-rich oil), corresponding to 0.4% of body weight for four weeks, on fatty acid composition and oxidative stress (lipid peroxidation and catalase activity) in mouse liver. The activities of aspartate aminotransferase (AST), alkaline phosphatase (ALP), alanine aminotransferase (ALT), and gamma-glutamyltransferase (GGT), biomarkers of tissue injury, were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…Studies about the chemical characterization of the bullfrog oil showed that the unsaturated fatty acids are present at lower concentrations (26.8%) than the saturated fatty acids (53.6%). Additionally, it was observed that these unsaturated fatty acids belong to the omega family [9,10,11,25]. Although these studies had identified the same compounds, it was possible to observe changes in their concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Studies about the chemical characterization of the bullfrog oil showed that the unsaturated fatty acids are present at lower concentrations (26.8%) than the saturated fatty acids (53.6%). Additionally, it was observed that these unsaturated fatty acids belong to the omega family [9,10,11,25]. Although these studies had identified the same compounds, it was possible to observe changes in their concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…6 fatty acids, in addition to cholesterol 9. 5 and ethyl-iso allocholate 3.5 6,9,10 . However, despite its broad popular use, especially against inflammatory conditions, there is a lack of scientific evidence supporting such therapeutic property.…”
mentioning
confidence: 99%
“…e study included beet, honey, onion, lemon, garlic, yarrow, and mint, demonstrating the wide variety of natural products used on asthma treatment in children [49]. Additionally, other natural-derived products have been widely cited in asthma treatment, such as natural oils from plants and animals, which can be obtained by different extraction process [52,53].…”
Section: Natural Products As Alternative Formentioning
confidence: 99%